Failure of Simply-Supported Flat Roofs by Ponding of Rain - Chinn, James (Engineering Journal, 1965)
A few structures supporting flat roofs have collapsed during rain storms even though they were apparently adequately designed and constructed. Such collapses have occurred in structures constructed of all three of the major building materials. The mechanism of failure is as follows: The structure has an initial deflection due to loads or initial downward camber or both, which creates a depression. Rain water ponds in the depression, causing additional deflection. This collects more water causing still more deflection. The cycle continues until the water spills over the edges or collapse occurs. The action can be analyzed in a step-by-step fashion asjust described. Mathematically, this corresponds to an infinite series. If the series converges, the structure will assume a final deflected position, and the water will spill over the edges. If the series diverges, the structure will, mathematically, continue to deflect as long as the rain continues.